Relation between hot flushes and endothelial dysfunction in postmenopausal women - YOLDEMİR, AHMET TEVFİK (My University, 2021)
Objective: To evaluate the relation between hot flushes and endothelial dysfunction in postmenopausal women: Study Design: A study was conducted on total of 132 women, who are between 45-65 years old and applied to Marmara University Pendik Research and Teaching Hospital Outpatient Clinic of Gynaecology, of whom 79 were postmenopausal women and 53 were premenopausal women. Of 132 participants, 32 experience no flushes, 22 mild, 40 moderate, and 38 severe. The demographic, metabolic, and hormonal characteristics were noted and all of the subjects completed within the duration of one week three-category hot flush diary that was conformed to FDA and EMEA guidelines, out of which none, mild, moderate, and severe groups were obtained. Carotid Intima Media Thickness (CIMT) and Flow Mediated Dilatation (FMD) on Brachial Artery measurements were completed on each one of the subject. A prospective case control study was performed. Only 76 Women agreed their blood to be drawn. Results: Mean FMD and CIMT values were similar in premenopausal and postmenopausal women (p=0.06). Blood biochemical values were similar in premenopausal and postmenopausal women. Mean FMD and CIMT values were similar both in the absence and the presence of the hot flushes, regardless of their severity. There was a direct correlation between the presence of the hot flushes, regardless of their severity and the time elapsed since menopause (p=0.001). Mean CIMT, FMD, blood biochemical values were similar both in the absence and the presence of the hot flushes, regardless of their severity. Conclusion: Direct correlation between the severity of hot flushes and the endothelial dysfucntion in postmenopausal was not found. There was a direct correlation between the presence of the hot flushes, regardless of their severity and the time elapsed since menopause (p=0.001).
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)